DISCUSSION OF RECENT PAPERS ON CARBONATED PERIDOTITE, BEARING ON MANTLE METASOMATISM AND MAGMATISM - Wyllie P.J. (My University, 1987)
The solidus temperature for peridotite-CO2 drops sharply within a narrow temperature interval, with increasing pressure, to an invariant point where dolomite becomes stable at the solidus. This geometry presents a barrier to some volatile-charged magmas rising through the lithosphere, with many petrological applications. The phase relationships are based on results in the model system CaO-MgO-SiO2-CO2, and peridotite-CO2-H2O. Two published sets of experimental results for the solidus of amphibole-dolomite-peridotite are here interpreted in terms of the topology of the system peridotite-CO2-H2O, with the conclusion that the two results yield quite different values for the pressure of the significant invariant point in peridotite-CO2: 17 kbar or 27 kbar (equivalent to 30 km in the upper mantle). Better definition of this pressure, and clarification of the topology of the intersecting stability fields for dolomite, amphibole and phlogopite with the peridotite-vapor solidus, are essential for understanding magmatic and metasomatic processes in the lithosphere, and the petrogenesis of alkaline magmas and associated carbonatites.